Znaczenie elektronicznej administracji dla funkcjonowania organizacji pozarządowych oraz innych podmiotów prowadzących działalność pożytku publicznego - Błażewski, Maciej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The provisions include a variety of ways of using the electronic means of communication which are connected with the activities of non-government organization and others charitable bodies. There are two aspects of this relationship: the active collaboration between these organizations and public bodies, and the gathering and publication of information of these organizations. Both aspects are relating to activities which are connected with transmission of information through electronic means of communication.
Keywords: public consultation; administrative proceedings; public information bulletin; electronic means of communication; non-governmental organization; e-government